Friction Stir Extrusion: A new process for joining dissimilar materials. (August 2015) - Evans, William T.; Gibson, Brian T.; Reynolds, Jay T.; Strauss, Alvin M.; Cook, George E.
Abstract: The need to join dissimilar materials such as aluminum and steel is prevalent in many industries. This paper investigates a new process called Friction Stir Extrusion (FSE) for joining aluminum and steel. The process uses Friction Stir Welding (FSW) to extrude aluminum into a premade concave groove cut into steel. FSE eliminates the concerns of intermetallic compounds and tool wear. This technique leads to a mechanically bound joint whose strength is determined by the mechanical bond between the steel and the extruded aluminum. Successful joints were created showing the FSE process has the potential for application to any combination of dissimilar materials.